2002
DOI: 10.1159/000046626
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Regulating Proteins and Prognosis in Diffuse Large B Cell Non-Hodgkin’s Lymphomas

Abstract: We evaluated the expression of apoptosis-regulating proteins (p53, Bcl-2, Bax, Bak and Mcl-1) in paraffin-embedded tissues of 33 patients with diffuse large B cell non-Hodgkin’s lymphoma , and assessed the relationship of these proteins to clinical outcome and response to chemotherapy. Our results showed that p53 expression was an independent immunohistochemical parameter related to a poor prognosis in these lymphomas. Bcl-2, Bax, Bak and Mcl-1 proteins, though highly expressed in almost all cases were not ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
5
13
0
1
Order By: Relevance
“…These results suggested that bcl-2 independent apoptosis is an important factor influencing cell death in many NHLs [22]. Overall results of previous studies [10,19,[22][23][24][25][26][27] and our results indicate that the expressions of bcl-2 family proteins are variable and heterogeneous in DLBCL. The dual effect of bcl-2 family proteins may show individual variation in the pathogenesis and prognosis of DLBCLs.…”
Section: Türk Et Al Apoptosis Proliferation In Large B-cell Lymphomasupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggested that bcl-2 independent apoptosis is an important factor influencing cell death in many NHLs [22]. Overall results of previous studies [10,19,[22][23][24][25][26][27] and our results indicate that the expressions of bcl-2 family proteins are variable and heterogeneous in DLBCL. The dual effect of bcl-2 family proteins may show individual variation in the pathogenesis and prognosis of DLBCLs.…”
Section: Türk Et Al Apoptosis Proliferation In Large B-cell Lymphomasupporting
confidence: 81%
“…(Turk J Hematol 2011;28: 15-26) Anahtar kelimeler: Büyük B-hücreli lenfomalarda apoptosis ve proliferasyon tosis and proliferation status in CD10/bcl-6/MUM1 immunophenotypic differentiation profiles is considerably limited. Although the immunohistochemical expression of the apoptosis-associated bcl-2 family proteins, bcl-2, bax, bak, and mcl1, was reported in DLBCLs [19][20][21][22][23][24][25][26][27][28], the expression levels of bcl-xl, bad, bid proteins and their relations with the status of apoptosis and proliferation were not extensively analyzed in these lymphomas [25].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some of these studies, including fewer than 65 patients, led to negative results, [37][38][39][40] more powerful analyses of more than 150 patients found that bcl-2 protein overexpression was independently related to relapse, 29 disease-free survival, 30,31 or overall survival. 32 In view of recent in vitro studies in human leukemia cell lines, 41,42 it has been suspected that a high bcl-2 expression may confer resistance to several antineoplastic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Variable percentages of bcl-2-positive tumor cells have been used to define bcl-2 overexpression. 37,38,40 However, major studies in noncutaneous diffuse large B-cell lymphomas consistently classified cases as bcl-2-expressing lymphomas if the protein was detected in more than 50% 31,32 or 60% 30 of tumor cells. In our patients with a PCLBCL, the 50% cutoff had a high clinical pertinence and a strong independent prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1 is highly expressed in some malignant B-cells (Ghia et al, 1998;Kitada et al, 1998;Soini et al, 1998;Agarwal and Naresh, 2002;Pagnano et al, 2002;Spets et al, 2002;Khoury et al, 2003), and this can correlate with clinical behaviour, such as failure to obtain complete remission in chronic lymphocytic leukemia (CLL) (Kitada et al, 1998). Importantly, enforced expression of Mcl-1 in transgenic mice promotes lymphomagenesis with a higher probability than Bcl-2 (approx.…”
Section: Introductionmentioning
confidence: 99%